The effect of incineration temperature to the chemical and physical properties of Ultrafine Treated Rice Husk Ash (UFTRHA) as Supplementary Cementing Material (SCM) - Saad, Siti Asmahani; Nuruddin, Muhd Fadhil; Shafiq, Nasir; Ali, Maisarah (Elsevier, 2016)
One of the important criteria of supplementary cementing material (SCM) in concrete is to possess high content of reactive silica that is essential in concrete strength development. Indeed, it is proven that rice husk ash (RHA) contains high amount of amorphous silica that is vital in the reaction of SCM in concrete. However, usage of conventional RHA is unfavourable in current concrete industry. One of the reason that hindered the utilization of conventional RHA nowadays is due to its properties inconsistency namely chemical and mineralogical properties. This phenomenon occurs due to sensitivity of the material towards burning temperature. In this regard, improvement on the RHA properties by introduction of thermochemical pretreatment prior to burning procedure is seen as an excellent way to reach the goal. In this paper, the effect of burning temperature to the characteristics of pretreated rice husk ash were tested. Raw rice husk was pretreated using 0.1N hydrochloric acid (HCl) and heated at 80oC. After that, the pretreated rice husk was mechanically activated by high energy planetary ball mill for 15 minutes at speed of 300rpm and ball-to-powder ratio (BPR) of 15:1. The effect of burning temperature to its chemical composition, particle size analysis, and microstructure properties of ultrafine treated rice husk ash (UFTRHA) were determined accordingly. As for amorphous silica content of the optimum sample was recorded as 97.00% incinerated at 700oC with three hours of pretreatment soaking duration. In terms of particle size analysis, it was also observed that, burning temperature of 700oC, pretreated at three hours were recorded to produce finest size of UFTRHA where D10, D50 and D90 were obtained as 1.417 μm, 4.493 μm and 14.884 μm respectively.